2020
DOI: 10.3390/su12229648
|View full text |Cite
|
Sign up to set email alerts
|

Active Road Studs as an Alternative to Lighting on Rural Roads: Driver Safety Perception

Abstract: Drivers, particularly with increasing age, cite driving at night as being problematic and feeling unsafe. Ultimately this may result in self-regulation and avoidance, with potentially negative health effects. The issue is commonly mitigated through provision of street lighting, but with it comes cost, environmental impact, and other negative effects. Research has suggested that provision of LED Active Road Studs may be of assistance to drivers at night. However, it is not known how implementation of this measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…For example, this phenomenon has been associated with interventions such as seat belts, anti-lock brakes, and the implementation of street lighting [29][30][31]. In the specific case of solar-powered road studs, if increases in driver confidence [17] were to translate to a corresponding increase in mean speed, this could result in increased crash rates [9][10][11][12][13][14]. The relationship between active road studs, other road features, and speed is therefore of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, this phenomenon has been associated with interventions such as seat belts, anti-lock brakes, and the implementation of street lighting [29][30][31]. In the specific case of solar-powered road studs, if increases in driver confidence [17] were to translate to a corresponding increase in mean speed, this could result in increased crash rates [9][10][11][12][13][14]. The relationship between active road studs, other road features, and speed is therefore of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…The studs feature high-powered LEDs which significantly increase the preview time of the road ahead and have been suggested as being of assistance to drivers in several road scenarios [15,16]. They have also been shown to have a positive impact on driver confidence [17]. However, if increased confidence were to result in a corresponding increase in speed, this could potentially compromise any road safety gains made.…”
Section: Introductionmentioning
confidence: 99%
“…if there is a bus lane at least in one direction 0, if there is no bus lane along the sec tion (2) Accidents that occurred on a given link over the examined period are aggregated. Based on this aggregation method, it is assumed that the contributing factors for accidents that occurred on the same link are similar, which may not be right all the time [51].…”
Section: Data Data Collectionmentioning
confidence: 99%
“…Road safety is one of the pillars in the Sustainable Development Goals, and it does not only explicitly address the issues related to good health and safety of the people, but it is also associated with the targets towards the development of sustainable cities [1]. Because of the scarce resources available, the implementation of the most effective road safety improvements is of paramount importance, so an analysis of each project's effectiveness cannot be avoided [2]. Efficiency analysis ought to apply a complex approach, including a socio-economic study [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the vehicles’ static time, although the in-out time counting is provided by cameras with number recognition installed at the entrance and exits of the parking system of crowded cities or multistory buildings, road flush-mounted sensors are used to detect occupancy [ 8 , 9 ] while advertising the results on a high visibility position via a color based system. Last but not least, road lane marking areas with no street lighting during the night can be enhanced with smart flushed sensors equipped with solar panels and LEDs, delivering a reliable sensing and marking [ 10 , 11 ]. Figure 1 illustrates the main applications of the smart road studs; presents specific examples of RF studs technologies such as those provided by Sensys Networks [ 12 , 13 ] and NEDAP [ 14 , 15 ]; describes the most commonly used methods for mounting the studs on the ground’s surface; outlines a general RF smart stud internal structure.…”
Section: Introductionmentioning
confidence: 99%